NIKAH DIBAWAH TANGAN DALAM PERSPEKTIF ISLAM - Arsyad Said (Maleo Law Journal, 2018)
Marriage is a very noble way to regulate the life of the household and the descendants and know each other, so that will open the way for mutual help-help. Marriage raises the Rights and duties of husband and wife reciprocity arranged very neatly, as well as the rights and obligations between parents and their children. In fact, not all Islamic societies follow the procedures or rules that apply. This is evident that some people still carry out unpublished marriage practices known as marriages under hand. Islamic law has raised the motives and goals of marriage to a higher and more noble level. If before guided by Islamic teachings the purpose of marriage is solely because driven by biological needs and continue life, by Islamic Shari'ah he was appointed with the motive of implementing sunnatullah with the basis of the purpose to worship Allah SWT